2014
DOI: 10.1093/nar/gkt1419
|View full text |Cite
|
Sign up to set email alerts
|

A widespread bacteriophage abortive infection system functions through a Type IV toxin–antitoxin mechanism

Abstract: Bacterial abortive infection (Abi) systems are ‘altruistic’ cell death systems that are activated by phage infection and limit viral replication, thereby providing protection to the bacterial population. Here, we have used a novel approach of screening Abi systems as a tool to identify and characterize toxin–antitoxin (TA)-acting Abi systems. We show that AbiE systems are encoded by bicistronic operons and function via a non-interacting (Type IV) bacteriostatic TA mechanism. The abiE operon was negatively auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
243
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(250 citation statements)
references
References 73 publications
6
243
0
1
Order By: Relevance
“…To date, over 23 lactococcal Abi systems have been identified, all of which are thought to interfere with different steps of the phage replication cycle (1,101). Recent studies have shown that certain toxin-antitoxin (TA) systems can also act as Abi systems upon activation by phage infection (104)(105)(106). For example, the plant-pathogenic bacterium Pectobacterium atrosepticum encodes the TA system ToxIN, which aborts phage infection.…”
Section: Abortive Infectionmentioning
confidence: 99%
“…To date, over 23 lactococcal Abi systems have been identified, all of which are thought to interfere with different steps of the phage replication cycle (1,101). Recent studies have shown that certain toxin-antitoxin (TA) systems can also act as Abi systems upon activation by phage infection (104)(105)(106). For example, the plant-pathogenic bacterium Pectobacterium atrosepticum encodes the TA system ToxIN, which aborts phage infection.…”
Section: Abortive Infectionmentioning
confidence: 99%
“…The results suggest that orf5 of pML21 may play a major role in stress tolerance in E. faecalis ML21, although the role of TA system in bacterial stress response are still remain debate [29,30]. Actually, recent reports indicated some bacterial abortive infection systems also function through TA mechanism [31,32]; this may be a explanation for the stress hypersensitivity of E. faecalis ML0 expressing orf3 and orf4. Interestingly, E. faecalis ML0-harboring pML23e showed significantly higher survival compared to other strains (Fig.…”
Section: Stress Tolerancementioning
confidence: 87%
“…In C. crescentus, the toxin SocB interferes with DnaN and thereby blocks the process of DNA replication (Aakre, Phung, Huang, & Laub, 2013). It has been proposed that TA systems benefit bacteria at a population level, for example, by inducing cell death or bacteriostasis in response to phage infection, thereby thwarting phage replication (Dy, Przybilski, Semeijn, Salmond, & Fineran, 2014). It has also been suggested that TA-induced suicide in response to nutrient starvation would set nutrients free to ensure the survival of the remaining cells.…”
Section: Regulation Of Dna Replication In Response To Genotoxic and Pmentioning
confidence: 99%